Exploratory practice in action: EFL teachers’ and students’ collaborative engagement in intensive reading activities - Sri, Melisa; Emilia, Emi; Safrina, Raden (Journal of English and Education (JEE), 2026)
This qualitative case study investigates how EFL teachers and students collaboratively enact Exploratory Practice (EP) principles in intensive reading instruction at an Indonesian university. Drawing on classroom observations, semi-structured interviews, and reflective journals, the research explores the pedagogical integration of EP’s seven key principles, including puzzle-posing, mutual development, and reflective inquiry. Findings reveal that EP transforms the reading classroom into a space for shared exploration, where both teachers and learners co-construct meaning, deepen engagement with texts, and foster a supportive learning community. Teachers shifted from delivering fixed content to facilitating dialogic discussions around learner puzzles, while students became more reflective and agentive in their reading practices. The enactment of EP led to improved teacher-student relationships, enhanced metacognition, and greater emotional investment in learning. However, challenges emerged, including time constraints, discomfort with open-ended inquiry, and misalignment with standardized assessments. Despite these tensions, the study underscores the potential of EP to humanize reading instruction by centering learner voice, inquiry, and well-being. This research contributes to the growing literature on practitioner research in language education, offering insights into the enactment of EP in skill-specific domains and advocating for more inclusive, inquiry-driven pedagogy in EFL contexts.